How Business Intelligence, Intellectual Capital, and Company Performance Increase Company Value? Leverage as Moderation - Renaldo, Nicholas; Suyono; Andi; Putri, Novita Yulia; Cecilia (Journal of Applied Business and Technology, 2023)
This study aims to analyze the role of leverage which moderates the effect of business intelligence, intellectual capital, and financial performance on firm value and is controlled by the variable firm size and sales growth in manufacturing industry companies on the IDX in 2013-2021. This study uses secondary data and panel data, a sample of 420 manufacturing industry companies in 2013-2021. The results of the first model study before moderation show that the independent variables of business intelligence, intellectual capital and company performance have a positive effect on firm value. However, for the leverage variable it has a negative effect on firm value, which shows that the higher the debt owned, the lower the company's value. The application of business intelligence can be done through the improvement of a good integrated system. Companies should optimize their intellectual capital. The use of debt to finance a company can increase the value of the company, this increase should be considered before making a decision by considering the risks that will arise and the cash flows that will be received.